PENGARUH AKSES PAJAK, PENGETAHUAN PAJAK DAN KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI SAMSAT SURABAYA BARAT - Kharina Apriliana Wati; Heru Tjahjono (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to describe and analyze the effect of product innovation, price and product quality on purchasing decisions at Waroeng Made Ali Nurdi. The sampling technique in this study used a non-probability sampling method (accidental sampling). Data were analyzed using SPSS tool. The results of the analysis based on the t test showed that partially Product Innovation, Price and Product Quality had a significant effect on purchasing decisions at Waroeng Made Ali Nurdi. Based on the F test, it is known that the product innovation, price and product quality variables have a significant effect on purchasing decisions at Waroeng Made Ali Nurdi. Thus, the manager of the Waroeng Made Ali Nurdi restaurant in West Surabaya is expected to further improve product innovation, price and product quality, so that it can influence consumer purchasing decisions.